Penetapan Jumlah Mahar Pada Masa Pandemi Covid-19 - Sahron, Muhammad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
The fundamental problem in this research is the determination of the amount of dowry during the Covid-19. This problem is motivated by the tendency of the prospective bride to determine the dowry as usual in society without seeing the impact of Covid-19 which affects the amount of the dowry itself, while the prospective groom wants the amount of dowry set to go down and consider the impact of Covid-19. which affects work and income. In this problem the researcher wants to see how the implementation of the determination of the dowry amount in the Covid-19 pandemic and what are the factors that cause changes to the dowry determination.The research methodology used is qualitative field research, namely research conducted by collecting primary and secondary data on the phenomenon that is happening directly. And this research which becomes the primary data is data obtained directly from the research subject, the primary data of the researcher is the people of, who are married., the secondary legal material for researchers is a dictionary of book translations. The tertiary legal materials are in the form of a legal dictionary, KBBI, and encyclopedia. Furthermore, the data collection techniques were carried out by interview, observation, and document study., the determination of the amount of dowry during the pandemic is still the same as before the pandemic period, the difference is that the amount has decreased. Second, factors that influence the amount of dowry 1) social status 2) Education 3) economy 4) Occupation. Third, Islam implies that the determination of the amount of dowry during the Covid-19 pandemic is not excessive. Because it will have a negative impact on the couple, and even result in the cancellation of the marriage.